2018
DOI: 10.1051/0004-6361/201833091
|View full text |Cite
|
Sign up to set email alerts
|

The angular momentum-mass relation: a fundamental law from dwarf irregulars to massive spirals

Abstract: In a ΛCDM Universe, the specific stellar angular momentum ( j * ) and stellar mass (M * ) of a galaxy are correlated as a consequence of the scaling existing for dark matter haloes ( j h ∝ M 2/3 h ). The shape of this law is crucial to test galaxy formation models, which are currently discrepant especially at the lowest masses, allowing to constrain fundamental parameters, e.g. the retained fraction of angular momentum. In this study, we accurately determine the empirical j * − M * relation (Fall relation) for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
205
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(243 citation statements)
references
References 48 publications
35
205
3
Order By: Relevance
“…In this case the observed scatter in R e would drive the one in j st ar , making the argument above circular. However, the constraints on the scatter in j st ar by Posti et al (2018b) quoted above, are found by direct integration of the observed rotation curves in the SPARC sample (Lelli et al 2016). It is also intriguing that, to first order, eq.…”
Section: Is the Mmw Model Consistent With Observed Ltgs Scaling Relatmentioning
confidence: 83%
“…In this case the observed scatter in R e would drive the one in j st ar , making the argument above circular. However, the constraints on the scatter in j st ar by Posti et al (2018b) quoted above, are found by direct integration of the observed rotation curves in the SPARC sample (Lelli et al 2016). It is also intriguing that, to first order, eq.…”
Section: Is the Mmw Model Consistent With Observed Ltgs Scaling Relatmentioning
confidence: 83%
“…Note that, for this plot, we do not compute the true specific stellar angular momentum from individual stellar particles, but rather estimate it exactly as for observations (Posti et al 2018). The magenta area with the dashed line shows the best fit of the observational data from Posti et al (2018), while the black line shows the best fit for the data of the models. The same functions as used by Posti et al (2018) are here applied to calculate j star and fit the data,…”
Section: Stellar Angular Momentum and Disk Vs Halo Populations Thin mentioning
confidence: 99%
“…The magenta area with the dashed line shows the best fit of the observational data from Posti et al (2018), while the black line shows the best fit for the data of the models. The same functions as used by Posti et al (2018) are here applied to calculate j star and fit the data,…”
Section: Stellar Angular Momentum and Disk Vs Halo Populations Thin mentioning
confidence: 99%
See 2 more Smart Citations